Methods for sampling manufactured domestic solid smokeless fuels in small consignments of mass 50 kg to 5000 kg either in bulk or in bags. Sampling of solid smokeless fuels other than coke Part 2, (31st January 1979) - British Standards Institution,
No abstract available